The implicit costs of trading in a jointly listed Irish equity - Dunne, Peter G. (Economic & Social Studies, 1994)
The paper invokes the concept of an implicit bid-ask spread in the Irish Stock Market and measures the consequent cost to traders as the expected gap between the price of sell and buy orders when these have been executed with a high degree of immediacy. Use is made of the spread estimator due to Hsia, Fuller and Kao (1994). The analysis shows that many important empirical tests (including the calculation of a stock's beta coefficient), are distorted by the presence of the implicit spread. A spin-off of a practical nature is the provision of guide-lines for limit-prices.
Keywords: Equities; Ireland; Stock market